Occupational health hazards and safety practices among the workers of tannery industry in Bangladesh - Islam, Rabiul; Hossain, Md Shakhaoat; Siddique, Md Abu Bakkar (Jahangirnagar University Journal of Biological Sciences, 2017)
In Bangladesh, workers of the tannery industries are commonly affected with several health hazards. The aim of this study was to determine the prevalence and patterns of health problems of the tannery workers, and to find out the factors associated with those health problems. A cross sectional studywas conducted on 316 general tannery workers (who work with raw hides and chemicals only) from 22 different tanneries in Hazaribagh, Dhaka, Bangladesh. A standardized, structured face to face interviewer-administered close ended questionnaire was used for data collection. Data were analyzed using descriptive statistics, logistic regression models and chi-square test. Around 63.3% of workers were affected with at least one health problems. Majority of the workers were suffering from skin problem (25.3%), gastrointestinal problem (8.5%), chronic headache (8.2%), allergies (5.7%), respiratory system problem (6.3%), cardiovascular problem (6.3%) and eye problem (3.5%). Only 36.7% respondents used personal protective equipment (PPE). The tanneries did not have any effluents or wastes treatment facilities. Smoking and monthly low household income were significantly associated with the morbidity of the tannery workers. The government should take adequate measures to mitigate the health hazards in the tannery industry. Jahangirnagar University J. Biol. Sci. 6(1): 13-22, 2017 (June)